2015
DOI: 10.3791/52341
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop Neuro-robotic Experiments to Test Computational Properties of Neuronal Networks

Abstract: Information coding in the Central Nervous System (CNS) remains unexplored. There is mounting evidence that, even at a very low level, the representation of a given stimulus might be dependent on context and history. If this is actually the case, bi-directional interactions between the brain (or if need be a reduced model of it) and sensory-motor system can shed a light on how encoding and decoding of information is performed. Here an experimental system is introduced and described in which the activity of a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Such operations have only a neurophysiological ontology; they are unable to directly alter or change the content of subjective experience (phenomenal consciousness) [25], and, according to Revonsuo [28] and Searle [68], they are totally outside of mental/subjective domain, and therefore they are entirely nonconscious. Indeed, as empirical studies have shown, the activity of neurons does not correlate reliably and predictably with higher cognition and levels of consciousness (for an extensive review and discussion, see [24,100]), even though, as was documented using in vitro neuron cultures (including so-called 'brain organoids') [101], they can perform a number of cognitive and memory operations, such as learning, source separation [102][103][104], and even controlling physical robotic systems and simulated video games [105,106]. When it comes to phenomenology, then ".…”
Section: Neurophenomenology Of Non- Un- and Sub-consciousnessmentioning
confidence: 99%
“…Such operations have only a neurophysiological ontology; they are unable to directly alter or change the content of subjective experience (phenomenal consciousness) [25], and, according to Revonsuo [28] and Searle [68], they are totally outside of mental/subjective domain, and therefore they are entirely nonconscious. Indeed, as empirical studies have shown, the activity of neurons does not correlate reliably and predictably with higher cognition and levels of consciousness (for an extensive review and discussion, see [24,100]), even though, as was documented using in vitro neuron cultures (including so-called 'brain organoids') [101], they can perform a number of cognitive and memory operations, such as learning, source separation [102][103][104], and even controlling physical robotic systems and simulated video games [105,106]. When it comes to phenomenology, then ".…”
Section: Neurophenomenology Of Non- Un- and Sub-consciousnessmentioning
confidence: 99%
“…Others used brain slices of different species to study the basic phenomena of learning on a cellular level (39). Neuron cultures were later shown to perform simple robotic tasks or demonstrate increased plasticity within a delayed closed-loop environment (40,41). The combination of brain cell cultures and computers has also been attempted: 2D cultured rat neurons displayed evidence of selforganized activity in a computational task (blind source separation) when supplied with electrical information (42).…”
Section: Introductionmentioning
confidence: 99%